Examining N cycling in the northern South China Sea from N isotopic signals in nitrate and particulate phases. Issue 8 (26th August 2017) - Yang, Jin‐Yu Terence; Kao, Shuh‐Ji; Dai, Minhan; Yan, Xiuli; Lin, Hui‐Ling
Abstract: Nitrogen sources and dynamics, one of the key issues in marine biogeochemical cycles, remain poorly constrained in marginal seas. Here we examine the nitrogen cycle in the northern South China Sea (SCS) by combining data from previous reports with a new data set of N isotopic compositions (δ 15 N) of nitrate, zooplankton, and sinking particles. Average δ 15 N in subsurface nitrate is 4.8 ± 0.3‰, similar to that of sinking particles (δ 15 Nsink of 4.4‰) through the euphotic zone (EZ) collected by floating traps and to documented mean (4.6‰) for long‐term mooring traps at 200 m. This along with oft‐observed shallow nitracline (<100 m) suggests that subsurface nitrate is the primary source of new N to support export production. Moreover, δ 15 Nsink at the bottom of the EZ resembles those of suspended particles (4.2 ± 1.0‰) and zooplankton (5.4 ± 1.0‰) inside the EZ. High similarity in δ 15 N among various types of particles including zooplankton in different size fractions in the EZ implies rapid N turnover in the ecosystem. In deep waters at 2000–3000 m, however, additional particulate N fluxes are found due to lateral transport, which contain 15 N‐depleted particles, resulting in a downward decreasing trend of δ 15 Nsink . Incorporation of lighter N by bacteria and selective export of picoplankton are proposed as alternative mechanisms contributing to low δ 15 Nsink in the deep waters. The significant δ 15 Nsink change in the deep water column makes the SCS different from most other marginal seas; thus, caution should be made when using sedimentary δ 15 N to reconstruct paleonitrogen processes. Key Points: High similarity in δ 15 N is found between subsurface nitrate and particles regardless of size fractions in the euphotic zone Lateral transport of 15 N‐depleted resuspended sediments contributes to a downward decreasing trend of δ 15 N in sinking particles The significant change of δ 15 N in sinking particles in the water column makes the South China Sea different from most other marginal seas